A reference floral transcriptome of sexual and apomictic Paspalum notatum - Ortiz, Juan Pablo Amelio (2017)
Fil: Fil: Ortiz, Juan Pablo Amelio. Universidad Nacional de Rosario. Facultad de Ciencias Agrarias; Argentina